Analisis Kandungan Residu Sulfametazin dalam Daging dan Hati Ayam secara Kromatografi Cair Kinerja Tinggi - Zuhelmi Aziz; Yulvian Sari; Raphaela Widiastuti; Lydia Septa Desiyana (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
Sulfamethazine is an antimicrobial and anticoccidiocis which usually used in poultry farm. The using of sulfamethazine to cattle has an accumulated residue effect on cattle products. An experiment of the decreasing motive of sulfamethazine residue concentration in chicken meat and liver has been carried out. One day old broiler chicken classified into 4 groups which are negative control, the positive control, the 7 days (7 days before the slaughtering day which on 36th day), and 5 days group (5 days before the slaughtering day which on 36th day). The last three groups are given sulfamethazine solution in oral 3 times a week with 0.2 ml/kg BW or 50 mg/kg BW dosage. After the giving of sulfamethazine stopped, each of those 4 groups slaughtered on 1st, 2nd, 3rd, 4th, 5th, 7th, 24th, 48th, 120th, 168th, 240th hour and then each of chicken meat and liver extracted and analyzed with high performance liquid chromatography (HPLC). The Sulfamethazine residue decreasing along with the increasing of time can be noticed from the experiment. In common, the decreasing of Sulfamethazine can be seen starting form 24th hour, then at 48th hour the sulfamethazine concentration stay at lower state and decrease along with the increasing of time.